Effectivity of Potassium and Fish Fertilizer on Leek Growth (Allium fistulosum L.) - Karo, Bina Beru; Marpaung, Agustina E (Journal of Tropical Horticulture, 2020)
Leek is one type of leaf vegetable that is commonly used for cooking vegetables or seasonings. Currently, it founded some problem in leek cultivation, including the production is low because the fertilization is not appropriate. The type and dosage of fertilizer can contribute to increasing production. This research aims to determine the dosage of potassium, and fish fertilizer is right for increased leek production. The research was conducted from January - March 2015 in the Berastagi experimental farm, with altitude Â± 1340 meters above sea level; the soil type was andisol. Experiments using a randomized block design (RBD) factorial with three replications. The first factor is the dosage of potassium fertilizer K0 (0 kg/ha), K1 (100 kg/ha), K2 (200 kg/ha), and K3 (300 kg/ha). The second factor is dosage fish fertilizer I0 (0 kg/ha), I1 (500 kg/ha), I2 (1000 kg/ha), and I3 (1500 kg/ha). The leek variety was used is local variety. The results showed that there is an interaction between the potash and fish fertilizers on leek plant height. Application potash fertilizer (K2O) dosage of 200 kg/ha and fish fertilizer dosage of 1000 kg/ha can increase the leek plant height 56,98 cm. Application potash fertilizer (K2O) dosage of 200 kg/ha can increase the stem diameter, length of stems, length of leaves, and fresh weight per plant. Application fish fertilizer dosage of 1000 kg/ha can increase the stem diameter, leaves length, fresh and dry weight per plant